(3JMaI GdeLO GdUQjM aj TQM cJGH GdaUjMs - (3CHh LYaQ TgGH GdOjf CMeO Hf jhSa GdagQi GddHdis; (3CHh GdYHGS CMeO Hf jMji Hf RjO KYdH GdTjHGfj Gdchaj GdfMhj,J (B291 (3g` s
(3ChdgG (B:s
(3hHYO , aEf GdhRjQ GdCLd CHh HcQ Hf GdhRjQ GdLdjd CTGQ Ydi HTQM TYGH GdaUjM ef JaSjQi dZQHjg , hTQMi deYGfjI aCLHJg Edi eGSCd s
(3BNQgG (B:s
(3bGd GdTjN CHh LYaQ (B: (3bGd GHf SjOg (B: (3GdOdLI HGdaJM hGdGScGf hCOdLhG SGQhG ef BNQg cdg , hbjd GdOdL Gddjd cdg ef Chdg Edi BNQg , McGg KYdH Yf CHj SdjeGf GdCYQGHi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B252s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs